THE ANALYSIS OF THE USE OF DIGITAL TECHNOLOGY LEARNING MEDIA IN ELEMENTARY SCHOOLS OF CILEUNYI DISTRICT - Eryca Pratiwi; Kristi Pratiwi; Marlina Sari; Salma Namiroh (JURNAL PAJAR (Pendidikan dan Pengajaran), 2020)
This study aims to analyze the use of digital technology learning media in elementary schools in the Cileunyi District. Digital technology is one proof of the development of technological progress in the 21st century. These technological advancements have influenced several fields, one of which is education. In this digital era, technology is involved in the field of education, especially in the learning process. Digital technology is now used as a learning medium. The use of digital technology as a learning medium means that the teacher has balanced knowledge with the technological advancements that occur. The research was conducted with a qualitative study by distributing questionnaires to 17 elementary schools in the district of Cileunyi. From the findings, it was known that all teachers have used digital technology as a medium of learning in elementary schools with different usage scales. The use of digital technology as a learning medium had an impact on teachers and the learning process undertaken. There were teachers who felt learning to be effective and innovative, yet there were still difficulties in using digital technology and felt the use of digital technology in elementary schools was less effective.